Meta-analysis of the association between alcohol consumption and abdominal aortic aneurysm. Issue 13 (7th September 2017) - Spencer, S M; Trower, A J; Jia, X; Scott, D J A; Greenwood, D C
Abstract: Background: Alcohol is a possible risk factor for abdominal aortic aneurysm (AAA), but evidence from individual studies is weak and inconsistent. Existing narrative reviews suggest the possibility of non-linear associations. The aim here was to quantify any association using a systematic literature review, followed by dose–response meta-analysis of prospective studies. Methods: MEDLINE, Embase and Web of Science were searched systematically to January 2017 for relevant prospective studies of alcohol consumption and AAA risk. Summary estimates of highest versus lowest levels of consumption, and linear and non-linear dose–response curves were quantified using random-effects models. Results: Eleven relevant cohorts were identified describing results from 3580 individuals with among 473 092 participants. Data were extracted from ten cohorts for meta-analyses of high versus low levels of alcohol consumption (risk ratio for AAA 0·93, 95 per cent c.i. 0·78 to 1·11; P = 0·4, I 2 = 47 per cent). The linear dose–response risk ratio for AAA, derived from 11 cohorts, was 1·00 (0·97 to 1·04) per 8 g alcohol per day ( P = 0·9, I 2 = 73 per cent). Non-linear dose–response results showed a tick-shaped curve with lower risk up to 2 units/day, but increasing risk beyond that ( P = 0·05). The increase in risk beyond 2 units/day was stronger in men than in women. Conclusion: Although the linear dose–response analysis revealed little evidence of an association between alcohol consumption and AAA risk, a tick-shaped trend in the association was observed. This non-linear dose–response analysis revealed reduced risks for alcohol consumption below 2 units/day, masking increased risks for 2 or more units/day. Abstract : Small increase above 2 units/day